Development of Mobile Machining Cell - Ringgaard, Kasper (Technical Report Mechanical Engineering, 2017)
This report covers some initial aspects of development of the mobile InnoMill machining cell. The new machining paradigm where the machine is mounted on the workpiece is compared to the old paradigm where the workpiece is mounted inside the machine, and differences are discussed. Parametric studies of the workpiece case study of the InnoMill project, the Vestas V112-3.0MW wind turbine hub, are performed to supply insight regarding load capacity etc. for the machine designers. The hub finite element model is validated using experimental results from Operational Modal Analysis performed on the hub. Furthermore, the InnoMill concept is described, and work regarding the 6 degree of freedom parallel kinematic manipulator which is present in the concept is performed. A numerical procedure accounting for base deflections due to static loading is proposed and implemented. Additionally, a six degree of freedom spring-mass model vibrational response is compared to vibrational response obtained from experiments on the 6 degree of freedom parallel kinematic manipulator at Aarhus University. The model, which is based on assumptions commonly found in literature, is rejected. Finally, an outlook for the remaining part of the PhD project is presented.